Occurrence and toxicity of microcystis aeruginosa (cyanobacteria) in the Paraná river, downstream of the Yacyretá dam (Argentina) - Forastier, Marina Elizabet (2016)
Fil: Forastier, Marina Elizabet. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.